Konsep Omnibus Law dan Implikasinya terhadap Pembentukan Hukum Pidana di Indonesia - Risman Setiawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The paradigm shift in the formation of legislation in Indonesia has undergone a significant phase following the enactment of Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 concerning the Formation of Legislation (UU PPP). Through the official recognition of the omnibus law technique, Indonesia paved the way for a legislative method that combines various legal substances into a single law. This study aims to critically analyze the impact of the application of the omnibus law technique on the quality of criminal law formation, with an emphasis on the clarity of norms, public participation, the deliberation process in the House of Representatives (DPR), and the legal legitimacy of the resulting regulations. The use of the omnibus law technique in the formation of criminal laws must be accompanied by strengthening public participation mechanisms, increasing the transparency of deliberations, and implementing quality testing of norms before enactment. Without this, legislative innovations originally intended to simplify the law have the potential to create new legal uncertainties in the national criminal law system.